Effect of cellulose ether as a thickening agent on the adhesive and rheological properties of mortars - Tien, Phan Van (Vietnam Journal of Science and Technology, 2014)
This paper presents an experimental study of adhesive and rheological properties of cement mortars proportioned with various contents of a water-soluble polymer admixture. To determine the adhesive properties the probe tack test was used. The results have been exploited to identify the adhesion strength, the cohesion strength and the support’ adherence force. It is found that the cohesion component displays a minimum when varying the polymer content. The behavior of the adherence force is more complex. The evolution of the adhesive force versus polymer content displays optima depending upon the tack test velocity. The rheological behavior of the mortars was also considered.